2000
DOI: 10.1520/jfs14635j
|View full text |Cite
|
Sign up to set email alerts
|

Cause and Manner of Death Among Users of Anabolic Androgenic Steroids

Abstract: Medicolegally investigated deaths among 34 male users of anabolic androgenic steroids (AAS) are described. Nine persons were victims of homicide, 11 had committed suicide, 12 deaths were judged as accidental and 2 as indeterminate. In two cases of accidental poisoning, the levels of pharmaceuticals and illicit drugs were considered too low to be the sole cause of death and AAS was considered part of the lethal polypharmacia. Chronic cardiac changes were observed in 12 cases. In tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
82
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(91 citation statements)
references
References 42 publications
8
82
0
1
Order By: Relevance
“…In particular, nalbuphine hydrochloride (Nubain) is popular among bodybuilders [183], and is associated with other substance misuse. In the clinical literature, naloxone has been used to treat AAS withdrawal in a bodybuilder [169], and AAS appear to interact with heroin in accidental drug overdose [172]. …”
Section: Opioidsmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, nalbuphine hydrochloride (Nubain) is popular among bodybuilders [183], and is associated with other substance misuse. In the clinical literature, naloxone has been used to treat AAS withdrawal in a bodybuilder [169], and AAS appear to interact with heroin in accidental drug overdose [172]. …”
Section: Opioidsmentioning
confidence: 99%
“…There is also a precedent for an interaction of androgens and opioids in humans [9,169,172]. In 2002, Arvary and Pope suggested that AAS could act as a gateway drug to opioid dependence [9].…”
Section: Opioidsmentioning
confidence: 99%
See 1 more Smart Citation
“…These episodes can escalate to extreme violence, including murder attempts (7). AAS abuse may lead to dependence, and drug discontinuation can cause severe withdrawal symptoms that may lead to suicide attempts (12,13).…”
Section: Submicromolar Doses Of S-norfluoxetine (S-nflx) That Are Insmentioning
confidence: 99%
“…However, when low doses of AS are used (l10-550mg per week), no increase in hostility could be detected [85]. At least 8 welldocumented cases of suicide have been linked to withdrawal from AS abuse [73], while analysis of CSF testosterone levels in 46 Swedish suicide attempters found lower Testosterone levels than in aggressive / violent patients in other studies [30]. AS abuse also appears to increase the risk of experiencing physical violence, including murder [54].…”
Section: Effects On Mental Statementioning
confidence: 99%